If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 8) = 5x + 44 Reorder the terms: 7(8 + x) = 5x + 44 (8 * 7 + x * 7) = 5x + 44 (56 + 7x) = 5x + 44 Reorder the terms: 56 + 7x = 44 + 5x Solving 56 + 7x = 44 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 56 + 7x + -5x = 44 + 5x + -5x Combine like terms: 7x + -5x = 2x 56 + 2x = 44 + 5x + -5x Combine like terms: 5x + -5x = 0 56 + 2x = 44 + 0 56 + 2x = 44 Add '-56' to each side of the equation. 56 + -56 + 2x = 44 + -56 Combine like terms: 56 + -56 = 0 0 + 2x = 44 + -56 2x = 44 + -56 Combine like terms: 44 + -56 = -12 2x = -12 Divide each side by '2'. x = -6 Simplifying x = -6
| -3(8p+2)-2(3-23p)=3(6+7p) | | (1-q)(1-q)=0 | | (1+q)(1+q)=0 | | 6=a/7 | | (29b-1)-7(4b+1)=-5 | | -f+5w+8= | | 5u-8/7=47/9 | | 49-9u-4/2 | | 5u-8/7=49-9u-4/2 | | x+3/5=40 | | 7/5x-4=-2/3x+6/5 | | -7/5w+1/3=-2/5w-2 | | -5/2u-7/2=4u+3/5 | | 8=-64 | | 4(2x-1)-(4x-3)=10 | | 4u-2/5=-4/5u-4/3 | | 5(1/2*y-3)-y=9 | | 3.5x+1.2=3.7-2.5x+3.7 | | (9x+8)(9x+3)= | | -1/2x-1/3=-4/5 | | (x-1)+2=2(x-3)+4x | | x=-5y^2 | | 3/2y-3=9 | | -1/3=6/5v-3/2 | | 5.7q-3.2-5.6q=-0.9q-5.1 | | 6+8x-4=2x+5-3 | | 4x+3y=380 | | 2x-1+x=4x-3 | | 4x-3y=380 | | 2X^2-56X-176=0 | | -4/y=8 | | 5x+4=4x-3 |